2005
DOI: 10.1051/animres:2004041
|View full text |Cite
|
Sign up to set email alerts
|

Ruminal degradability of corn forages depending on the processing method employed

Abstract: -The in sacco degradabilities of starch and fibre in corn were compared between kernel grains and the whole corn plant before and after ensiling using the nylon bag technique. The same plants were used, in order to exclude the effects of genotype or maturity at harvest. The incubation time course was carried out over 48 h on four cannulated dairy cows. The effective degradability of starch was lower in kernel grains (70.2%) than in the whole plant before (83.9%) and after (92.3%) ensiling. Starch degradation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
19
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 31 publications
6
19
1
Order By: Relevance
“…Therefore, ADICP and NDICP appeared to be ill-suited for mak- ing indirect inferences with regard to starch digestibility in HMC. Data from this study substantiates the hypothesis that hydrophobic zein proteins, especially γ-zeins, in the starch-protein matrix are degraded during the ensiling process as proposed by Philippeau and MichaletDoreau (1998) and Jurjanz and Monteils (2005). The γ-zeins lay peripheral to and cross-link with α-and δ-zeins in the starch-protein matrix, thereby adhering starch granules together and ostensibly forming the starch-protein matrix (Buchanan et al, 2000;Mu-Forster and Wasserman, 1998).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Therefore, ADICP and NDICP appeared to be ill-suited for mak- ing indirect inferences with regard to starch digestibility in HMC. Data from this study substantiates the hypothesis that hydrophobic zein proteins, especially γ-zeins, in the starch-protein matrix are degraded during the ensiling process as proposed by Philippeau and MichaletDoreau (1998) and Jurjanz and Monteils (2005). The γ-zeins lay peripheral to and cross-link with α-and δ-zeins in the starch-protein matrix, thereby adhering starch granules together and ostensibly forming the starch-protein matrix (Buchanan et al, 2000;Mu-Forster and Wasserman, 1998).…”
Section: Discussionsupporting
confidence: 90%
“…Philippeau and Michalet-Doreau, (1998) observed that ensiling grains increased ruminal starch degradability and hypothesized that ensiling increases accessibility of starch granules to rumen microorganisms, because hydrophobic zein proteins were degraded. Likewise, Jurjanz and Monteils (2005) observed ruminal degradability of starch to be greater for corn kernels after ensiling (92.3%) as compared with that of unensiled corn kernels (70.2%). The ensiling process improved starch degradation by increasing the rapidly degradable starch fraction (80.7 vs. 65.6%) and the starch degradation rate (12.4 vs. 8.0%/h).…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…Ensiling of ground corn grain increases ruminal degradability of starch, which may suggest that the process of silage fermentation can increase the access of rumen bacteria to starch granules by removing the protein barrier (PHILIPPEAU; MICHALET-DOREAU, 1998). The ensiling process of high-moisture corn grain increased the ruminal degradability of starch by 22.1% compared with dried corn grains (JURJANZ; MONTEILS, 2005). The effect of ensiling on the degradability of corn starch may occur by increasing the rapidly degradable fraction (fraction A) and the rate of starch degradation of corn grains in the silage.…”
Section: Introductionmentioning
confidence: 99%